Implementasi Program Kesejahteraan Karyawan dan Dampaknya terhadap Produktivitas Usaha (UMKM) Kripik Balado Salsabila - Olyvia Uqya Marlen; Popi Anugerah; M Fahri Suryadi Fathan; Vicky Brama Kumbara (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This research aims to analyze the implementation of employee welfare programs and their impact on business productivity at the UMKM Kripik Balado Salsabila. Employee welfare programs include providing incentives, work facilities, training and a supportive work atmosphere. The research results show that the implementation of employee welfare programs significantly increases employee motivation, loyalty and performance. This increase has a positive impact on business productivity, as can be seen from production efficiency and increased turnover. This study concludes that employee welfare programs are a strategic investment for UMKM to achieve sustainability and competitiveness in the market.